THE EFFECT OF GUIDED IMAGERY RELAXATION TOWARDS PAIN LEVEL OF POST-SURGICAL CAESAREAN SECTION PATIENTS IN GENERAL HOSPITAL MUHAMMADIYAH SITI AMINAH BUMIAYU, INDONESIA - Khusana Rahma (Proceedings of the International Conference on Applied Science and Health, 2017)
Background: Pain is one of the diagnostic study found in the post-surgical phases, including sectio caesaria. Sectio caesaria surgery causes tissue and cell damage that result in the release of painful substances such as bradykinin, lactic acid and prostaglandins. These substances cause nociceptor impulses and lower the pain threshold, causing the sensitivity of pain receptors. One of the interventions that can be done to relief the pain is through the use of guided imagery relaxation techniques. This method was one of the non- pharmacological treatments to lessen the pain by using words and positive imagination. Aim: To compare the pain level of the patients with post operation of sectio caesaria, before and after guided imagery relaxation. Methods: The research design was pre-experimental with one pre-test group of 30 patients. The population in this study were post-operative patients of sectio caesaria at Muhammadiyah General Hospital Siti Aminah Bumiayu, where in October 2014 the number of cure patients treated in the Marwah Room were 55 patients. The respondents’ samples were taken from their surgical procedures of sectio caesaria. The sampling technique was purposive sampling. Conclusion: Guided imagery relaxation had a significant effect towards the levels of post-operative sectio caesaria’s pain. Nurses can apply guided imagery relaxation as an intervention and develop the related standard operational procedure (SOP) to ease the patients’ pain problem.